Analysis of the effect of airline brand image, airline trust, service quality and price fairness on airline loyalty with passenger satisfaction as a mediation in PT Citilink Indonesia - Purba, Revail Edianto; Ginting, Ari Mulianta (Institute of Computer Science (IOCS), 2025)
Transportation plays an important role in economic growth, especially in urban areas. With the vastness of Indonesia and the many islands and existing developments, air transportation has become one of the main transportations, creating competitive competition for airlines which then triggers efforts to maintain passenger loyalty. This study aims to examine the effect of airline brand image, airline trust, service quality, price fairness and passanger satisfaction on airline loyalty of the Citilink Indoesia. This study was conducted quantitatively on 238 respondents domiciled in Jabodetabek, Indonesia. The results of this study indicate that trust, service quality and satisfaction have a significant effect on airline loyalty while brand image does not have a significant effect on airline loyalty, in addition brand image, trust and service quality also have a significant effect on satisfaction of Citlink passengers in Jabodetabek